IMPLEMENTASI PENDIDIKAN KARAKTER PADA KURIKULUM 2013 (STUDI DI MADRASAH ALIYAH NEGERI KOTA SERANG) - Gunawan, Agus; Puji Rosa, Nurjanah (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2020)
The purpose of this study is to know the character education in MAN Kota Serang, to know the implementation of character education in Curriculum 2013, and to know the strategy of headmaster of MAN in Serang City in the implementation of character education in the curriculum 2013. The research method used in this research is qualitative method, with descriptive analytic research design. Data collection techniques used are, in-depth interviews, documentation and observation. The results of this study states that the implementation of character education in MAN Kota Serang has been well realized. The 2013 curriculum that has been implemented in MAN Kota Serang becomes a reference that makes it easier for all stake holders in applying character education in School. The content of the character values embedded in the students themselves, both at the time of learning activities and during school activities, among others: such as responsibility, courtesy, discipline, and have a high spiritual spirit (religious), honesty, citizenship, confident has become a character that is formed in the students of Madrasah Aliyah in Serang City. Supporting activities or programs for the implementation of character education in schools are well implemented, with several supporting factors ranging from leadership to all stake holders in schools, as well as facilities and infrastructure that support the needs of students to apply life skills in accordance with their potential.